LC/MS- and GC/MS-based metabolomic profiling to determine changes in flavor quality and bioactive components of Phlebopus portentosus under low-temperature storage - Li, Xiao-Bei; Hu, Chen-Menghui; Li, Cai-Hong; Ji, Guang-Yan; Luo, Shun-Zhen; Cao, Yang; Ji, Kai-Ping; Tan, Qi; Bao, Da-Peng; Shang, Jun-Jun; Yang, Rui-Heng (Frontiers in Nutrition, 2023)
Introduction Low temperature is the most common method used to maintain the freshness of Phlebopus portentosus during long-distance transportation. However, there is no information regarding the nutritional changes that occur in P. portentosus preserved postharvest in low temperature. Methods In this study, the changes in flavor quality and bioactive components in fruiting bodies stored at 4 °C for different storage periods were determined through LC/MS and GC/MS analyses. Sampling was performed at 0, 3, 5, 7, and 13 days storage. Results and Discussion Based on the results, the metabolites present in caps and stipes were different at the same period and significantly different after 7 days of storage. A total of 583 and 500 different metabolites were detected in caps and stipes, respectively, and were mainly lipids and lipid-like molecules, organic acids and derivatives, organic oxygen compounds and others. Except for prenol lipids and nucleotides, the expression levels of most metabolites increased with longer storage time. In addition, geosmin was identified as the major contributor to earthy-musty odors, and the level of geosmin was increased when the storage time was short. Conclusion The variations in these metabolites might cause changes in flavor quality and bioactive components in P. portentosus. Variations in these metabolites were thoroughly analyzed, and the results revealed how storage processes affect the postharvest quality of P. portentosus for the first time.